P01.114 Expression and prognostic value of the immune checkpoint molecule galectin-9 in glioblastomas. (19th September 2018) - Andersen, S; Knudsen, A M; Dahlrot, R H; Sørensen, M D; Kristensen, B W
Abstract: Background: Glioblastomas are highly malignant with a median survival time below15 months. Immunotherapy has shown promising results in different types of cancer, and novel therapies targeting PD-1/PD-L1 signalling have been approved for treatment of patients with melanoma and lung cancer. Galectin-9, a checkpoint molecule, may be a potential therapeutic target. Galectin-9 and its receptor, TIM-3, are involved in cancer cell aggregation, induced T-cell apoptosis, and tumor progression. Previous studies indicate that galectin-9 may be expressed in high-grade gliomas. The aim of this study was to investigate the expression and prognostic value of galectin-9 in glioblastomas. Material and Methods: Tissue from 166 glioblastoma patients from the Region of Southern Denmark glioma cohort was included. The tissue sections were immunohistochemically stained with anti-galectin 9 antibody. Image analysis and area fraction quantification of the stainings were performed using the image analysis software, Visiopharm. Results: Galectin-9 was highly expressed in most glioblastomas, especially in cells with microglial and macrophage morphology, but some glioblastomas had a very limited expression. The mean positive area fraction was 0.06 (range 0.01–0.32). When dichotomized at the median no difference in the median overall survival was observed. Galectin-9 was not associated with overall survival (HR= 0.97, p=0.8) in multivariate analysis including age, performance status, post-surgical treatment and MGMT status. Conclusion: The galectin-9 protein was expressed in most glioblastomas. Targeting of galectin-9 may therefore be of potential value in most glioblastoma patients in order to obtain immune-mediated anticancer effects.Galectin-9 expression was not associated with patient survival. Potential co-localization of alectin-9 and its receptor TIM-3 will be investigated in our future work, as will the correlation with PD-L1 expression, to discover potential strategies for combination treatment.